Determination method of trace amount of arsine and phosphine in ethylene and propylene based on gas chromatography-mass spectrometry - HUO Daa, CHEN Feia, LAI Jin-bob, SHI De-junc, WANG Chun-yana, CAO Qinga (Hecheng xiangjiao gongye)
"A method for simultaneous determination of trace amount of arsine and phosphine in ethylene and propylene was developed based on gas chromatography-mass spectrometry, and the limit of detection, linear range, recovery rate and repeatabi-lity of the method were investigated. The results showed that the limit of detection of this method for arsine could be as low as 0.682 μL/m3 and the correlation coefficient between peak area and volume concentration was 0.999 5 within the volume concentration range of 4.955-99.100 μL/m3, the deviations between the test value and the actual value of samples with different concentrations were all within 7% and the relative standard deviation of the three measurement results was 1.14%.The limit of detection of this method for phosphine could be as low as 0.677 μL/m3 and the correlation coefficient between peak area and volume concentration was 0.999 7 within the volume concentration range of 5.000-100.000 μL/m3, the deviations between the test value and the actual value of samples with different concentrations were all within 10% and the relative standard deviation of the three measurement results was 1.20%. The chromatographic column system used in this method was simple, the limit of detection was low and the determination process was convenient and fast, and this method could provide a new analytical means for the quality monitoring of polymerization-grade ethylene and propylene monomers."